Advanced Distillation Technologies : - Kiss, Anton Alexandru. (John Wiley & Sons Inc, 2013)
Content: Covers the background, recent developments, fundamental principles, design and simulation, detailed cases of separations in DWC, and future trends"-- Provided by publisher.